The Surfactant Protein D (SP-D) Serum Levels in Limestone Mining Worker - Sita Laksmi Andarini; Anna Yusrika; Sri Wening Pamungkasningsih; Farhan Hilmi Taufikulhakim; Ahmad Hudoyo; Widhy Yudistira Nalapraya; Agus Dwi Susanto (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: Limestone is sedimentation rocks consist of minerals calcite and aragonite, often contains silica, and fossils, commonly used in building materials. Limestone mining workers are at high risk to pneumoconiosis. Surfactant protein D(SP-D) is part of collectin family, and served as innate immune system of pathogen recognition receptor (PRR). SP-D level were usually increased in fibrotic lung disease. In this study, we sought the serum level of SP-D as marker for early pneumoconiosis in limestone worker in Indonesia.Method: This study was cross-sectional observational study. Participant of the study were 65 limestone workers, willing to participate in this study by signing informed consent, were questionnaire, and blood sample were collected to measure SP-D level by ELISA.Results: This study found that characteristic subjects dominated by male with the median of age was 42 years old and last education mostly elementary school. Majority duration of working <6 years and time working in a day >8 hours per day. The limestone mining workers mostly did not wear mask and had normal weight group. Majority limestone mining workers ever smoker, mean SP-D level in limestone workers was (66.3±5.5ng/mL), slightly higher than normal subject. Smoking status, gender, working hour were correlated with higher SP-D level.Conclusion: Although not statistically significant, the SP-D serum levels in limestone mining workers might be used as monitoring for early screening for pneumoconiosis in limestone workers.